Solvability of Implicit Fractional Order Integral Equation in ℓp1≤p<∞ Space via Generalized Darbo's Fixed Point Theorem. (20th May 2022) - Haque, Inzamamul; Ali, Javid; Mursaleen, M.
Abstract : We present a generalization of Darbo's fixed point theorem in this article, and we use it to investigate the solvability of an infinite system of fractional order integral equations in ℓ p 1 ≤ p < ∞ space. The fundamental tool in the presentation of our proofs is the measure of noncompactness mnc approach. The suggested fixed point theory has the advantage of relaxing the constraint of the domain of compactness, which is necessary for several fixed point theorems. To illustrate the obtained result in the sequence space, a numerical example is provided. Also, we have applied it to an integral equation involving fractional integral by another function that is the generalization of many fixed point theorems and fractional integral equations.